2007
DOI: 10.1111/j.1750-3841.2006.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Honey Amylase

Abstract: The major alpha-amylase in honey was characterized. The optimum pH range and temperature were determined for the enzyme as 4.6 to 5.3 and 55 degrees C, respectively. The enzyme was stable at pH values from 7 to 8. The half-lives of the purified enzyme at different temperatures were determined. The activation energy for heat inactivation of honey amylase was 114.6 kJ/mol. The enzyme exhibited Michaelis-Menten kinetics with soluble starch and gave KM and Vmax values of 0.72 mg/mL and 0.018 units/mL, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The latter may occur due to the formation of acid and as a result cause fermentation. Babacan & Rand (2007) reported that amylase enzyme conserved 80% of its activity at 55 °C and its maximum activity was observed at 38–40 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The latter may occur due to the formation of acid and as a result cause fermentation. Babacan & Rand (2007) reported that amylase enzyme conserved 80% of its activity at 55 °C and its maximum activity was observed at 38–40 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These studies did not assess amylase activity or investigate the conditions needed to inactivate amylase in starch suspensions. Honey amylase was found to cause viscosity loss in a waxy maize suspension at 40℃ (Babacan et al, 2002;Babacan and Rand, 2007). They reported that the amylase could be inactivated by heating the honey to 83℃.…”
Section: Results and Discussion α-Amylase Activity At High Temperaturesmentioning
confidence: 99%
“…The pH value of honey is around 3.9 and water activity (WA) of honey ranges between 0.56 to 0.62 (Hassapidou et al, 2006;Babacan S and Rand AG., 2007). Since honey has high level of fructose it was utilized as a natural sweetener from ancient period and it has 25% more sweetness than tablet sugar (Babacan and Rand, 2007;Pataca et al, 2007). Honey was known to possess various pharmacological properties viz anti-inflammatory, anti-bacterial, antioxidant etc.…”
Section: Introductionmentioning
confidence: 99%